Global supply chain security - Giermanski, James R. (The Scarecrow Press, Inc., 2013)
The author explores the potential impact of port-related catastrophic events in the United States and their effects worldwide, concentrating, in particular, on the United States' contribution to global container security. He underscores the vulnerabilities in the supply chain that U.S. government agencies have ignored, avoided, and even denied.